Improving soil acidity on peat soil through rice husk ash and rabbit urine biofertilizer application - Muharram, Muhammad; Yoseph Samago, Tarekegn; Putra Garfansa, Marchel (Environmental and Agriculture Management, 2025)
Low pH and limited nutrient availability in peat soil hinder optimal mustard growth, underscoring the need for effective organic amendments. This study aimed to evaluate the effects of rice husk ash and rabbit urine liquid organic fertilizer (POC) on soil pH and mustard plant growth in peat media. The experiment was conducted using a Completely Randomized Design (CRD) with two factors: rice husk ash (0, 15, 20, and 25 tons/ha) and rabbit urine POC (0, 15, 30, and 45 mL/L), replicated three times for a total of 48 polybag units. Prior to transplanting, rice husk ash was incubated in the soil for one week to increase pH. Mustard seedlings were grown for 28 d, and POC was applied weekly for three weeks as both foliar and soil treatments. Growth parameters measured included plant height, leaf width, leaf number, and fresh biomass. The results showed that both rice husk ash and rabbit urine POC significantly influenced all measured growth parameters. The highest fresh weight (40.22 g) was observed in the P2K1 treatment (20 tons/ha ash + 30 mL/L POC), while the best overall vegetative performance was recorded in P3K2. It can be concluded that the integrated use of rice husk ash and rabbit urine POC can effectively improves peat soil properties and enhances mustard growth. This study highlights the potential of utilizing agricultural waste-based organics to support sustainable crop production in acidic soil environments.